2020
DOI: 10.3390/ani10061053
|View full text |Cite
|
Sign up to set email alerts
|

Intramammary Infections in Heifers—Time of Onset and Associated Risk Factors

Abstract: To reduce the negative effects of mastitis in dairy heifers in early lactation on the future milking performance, the aim of this study was to define the time-related period of intramammary infections and to relate this to risk factors at heifer and quarter level for intramammary infections and subclinical mastitis. In total, 279 German Holstein Frisian heifers in three farms in Northern and Eastern Germany were included in this study. Quarter milk samples for cytomicrobiological examination were collected 3 ±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0
5

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 39 publications
(69 reference statements)
1
19
0
5
Order By: Relevance
“…Additionally, those cows with a lower BCS after calving showed rarer udder edema than cows with a BCS greater than 3.5 after calving. Nitz et al [ 31 ] demonstrated the same occurrence in heifers, with prolonged udder edema related to an increased risk of developing IMI with NAS and coryneforms three days after calving. Piepers et al [ 32 ] also identified udder edema as an important risk factor for IMI, with contagious major pathogens in heifers.…”
Section: Discussionmentioning
confidence: 92%
“…Additionally, those cows with a lower BCS after calving showed rarer udder edema than cows with a BCS greater than 3.5 after calving. Nitz et al [ 31 ] demonstrated the same occurrence in heifers, with prolonged udder edema related to an increased risk of developing IMI with NAS and coryneforms three days after calving. Piepers et al [ 32 ] also identified udder edema as an important risk factor for IMI, with contagious major pathogens in heifers.…”
Section: Discussionmentioning
confidence: 92%
“…This finding is in line with previous studies indicating that increased age 6. Final multivariable multinomial logistic regression analysis of factors from calf to calving associated with being a herd with a large proportion of primiparous cows with low SCC at first and second milk recording after calving (LL herds), a large proportion of primiparous cows with high SCC at first milk recording and low SCC at the second milk recording (HL herds), or a large proportion of primiparous cows with high SCC at first and second milk recording (HH herds) after calving (n = 167, pseudo R 2 = 0.42) at first calving is associated with poorer udder health in early lactation (Waage et al, 1998;Eastham et al, 2018;Nitz et al, 2020), although the opposite has also been found (De Vliegher et al, 2004). The reasons why age at calving is important are not clear.…”
Section: Discussionmentioning
confidence: 99%
“…It may be hypothesized that differences are due to better routines and planning in LL and HL herds. However, Nitz et al (2020) suggested that the BCS before calving, which may increase with age at calving, and a larger loss of BW in early lactation in primiparous cows with high BCS resulting in a more pronounced negative energy balance with negative effects on the immune response, can be of importance. This suggestion is in line with our previous finding that higher concentrations of nonesterified fatty acids before calving were associated with higher SCC in primiparous cows at first test milking (Nyman et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…No entanto, os programas comuns de prevenção e controle da doença não abordam a mastite de novilhas em seus protocolos de boas práticas (Nitz et al, 2020). Isto deixa uma lacuna em aberto, uma vez que infecções intramamárias (IIM) antes do parto e no início da lactação podem comprometer o desenvolvimento da glândula.…”
Section: Revisão De Literaturaunclassified
“…Isto deixa uma lacuna em aberto, uma vez que infecções intramamárias (IIM) antes do parto e no início da lactação podem comprometer o desenvolvimento da glândula. Como consequência, além de afetar negativamente a saúde do úbere, pode aumentar o risco de descarte precoce do animal Nitz et al, 2020).…”
Section: Revisão De Literaturaunclassified